Variación craneofacial de los primeros habitantes de las pampas argentinas: implicancias para el poblamiento de América - Menéndez, Lumila Paula (2017)
Craniofacial comparisons between the earliest and latest human skeletons of America have suggested the existence of a complex scenario underlying the biological evolution of American populations. Particularly, these studies proposed migratory processes -physical movement of large number of people across the space- as the main factor behind the craniofacial variation in America. At the end of 19th and the early 20th centuries, Florentino Ameghino initiated the discussions on the high antiquity of humans and their ancestors on the extensive grasslands of the pampean region. However, only recently, the importance of Argentinean pampas samples to discuss the evolution of American populations had been revisited because of the radiocarbon dating of eight samples of human bones from seven archaeological sites excavated by Ameghino and collaborators. In this study, we present a review and analysis concerning those early samples from the pampean region measured and studied by Héctor Pucciarelli and colaborators in the last years. The early samples were compared against Late Holocene samples, showing pronounced differences. The analyzed samples present the greatest morphological variation when plotted with other early American samples. However, using solely cranial morphometric differences it is hard to support the hypotheses that morphological variations between early and late American samples are related to migratory processes or other factors. Molecular evidence from the same samples suggests population continuity. Although craniometric evidence was very important to understand the human peopling and diversification in South America, it is necessary to jointly consider further evidences (e.g., archaeological and molecular).